Ebook acquisition in a puerto rican academic library: conditions of use and user’s preferences - Montalvo-Montalvo, Marilyn; Lebrón-Ramos, Jeannette (Revista General de Información y Documentación, 2014)
The aim of this paper is to determine the acceptable conditions of use for the purchase of ebooks by the Library System of the University of Puerto Rico, Río Piedras (SB). The analysis is based on the conditions of use set by vendors of ebooks with which the SB has subscriptions or purchase with perpetual access agreements. Moreover, usage statistics of some of the available platforms and the results of a survey conducted by the SB in order to find out the views of the students about ebooks, are also discussed.
Keywords: Academic Libraries; Conditions of Use; Ebook; Puerto Rico; Users; Vendors